Aqueous polyurethane phase change aerogel glass and method of making the same

CN119550699BActive Publication Date: 2026-11-03HUBEI XINGRUI SILICON MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411485656.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2026-11-03
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

Traditional building envelopes struggle to achieve thermal balance based on indoor and outdoor temperatures and solar energy, resulting in high energy consumption. Furthermore, existing phase change materials suffer from low thermal conductivity and edge leakage issues in their applications.

Method used

Waterborne polyurethane phase change aerogel glass is used, which combines the advantages of polyurethane and phase change materials by compositing the glass with hydrophobic and hydrophilic aerogel layers. This allows for the absorption and release of heat, regulating indoor temperature and reducing energy consumption.

Benefits of technology

It efficiently absorbs and utilizes solar energy in winter and isolates solar radiation heat in summer, significantly reducing building energy consumption and improving energy efficiency and comfort.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119550699B_ABST
    Figure CN119550699B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of water-based polyurethane phase change aerogel glass, and the water-based polyurethane phase change aerogel glass comprises a silica aerogel thermal insulation layer with a water-based polyurethane phase change hydrophobic-hydrophilic double-layer structure. The aerogel glass is prepared through the steps of hydrophobic gel preparation, hydrophilic gel preparation, solvent replacement, supercritical drying, phase change material adsorption and encapsulation. The prepared aerogel glass realizes active adjustment of indoor temperature through the water-based polyurethane phase change process, greatly reduces the energy consumption required for indoor heating and refrigeration by isolating the influence of external temperature on the indoor temperature, and can play a good thermal insulation role when the temperature difference between the inside and outside of the building is large. The polyurethane phase change material and the aerogel are combined, the overall thermal insulation performance is greatly improved, the comprehensive performance of the polyurethane phase change aerogel glass is improved, and a new solution is provided for building energy saving.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aerogel glass technology, specifically relating to an aqueous polyurethane phase change aerogel glass and its preparation method. Background Technology

[0002] Building energy consumption primarily stems from energy expenditures on heating, air conditioning, ventilation, and hot water supply. Most buildings are high-energy-consuming and non-energy-efficient. Building energy conservation has become a crucial aspect of developing a conservation-oriented society and a circular economy. It aims to reduce energy consumption by using energy rationally and improving energy efficiency while ensuring building comfort. According to statistics and estimates of energy consumption in different types of buildings, nearly 50% of building energy consumption is directly or indirectly caused by the building envelope. Therefore, researching and optimizing the design of building envelopes is key to building energy conservation. However, due to the fixed thermophysical parameters, traditional building envelopes struggle to achieve thermal balance based on indoor and outdoor temperatures and solar energy.

[0003] Currently, it has been found that applying phase change materials (PCMs) to building envelopes is more energy-efficient than conventional buildings. Organic solid-liquid PCMs possess advantages such as a wide phase change temperature range, stable chemical properties, high latent heat, and low cost. However, their low thermal / electrical conductivity hinders solar energy utilization. Furthermore, they require encapsulation or shaping, and issues such as edge leakage, volatilization, or corrosion limit their application. Solid-solid PCMs, on the other hand, remain in a solid state throughout the phase change process, enabling both heat absorption and release. Variable reflectivity building envelopes integrating solid-solid PCMs and porous ceramic thermal storage serve as a novel building envelope design. They can efficiently absorb and utilize solar energy in winter and effectively reduce solar radiation heat gain in summer, thereby reducing building energy consumption and possessing significant application value.

[0004] Within the technological framework of the phase change aerogel glass industry, aerogel material technology and phase change material technology have demonstrated remarkable development trends. In terms of aerogel material technology, the preparation technology of nanoporous aerogels has gained attention since 2018, aiming to develop new materials with excellent thermal insulation properties. Subsequently, the research and development of high-strength, high-transparency aerogels has also become a focus, with the expectation of improving the mechanical properties and light transmittance of the material while maintaining excellent thermal insulation performance.

[0005] In the field of phase change materials (PCM) technology, the optimization of PCM cold storage materials and the modification of PCM heat storage materials aim to improve the energy storage efficiency and density of PCM materials. With continuous technological advancements, PCM intelligent temperature-regulating materials achieve active temperature regulation through the phase change process, showing broad application prospects in areas such as building energy conservation and electronic product heat dissipation. In summary, the cross-disciplinary integration of aerogel materials and PCM technologies brings new development opportunities to the PCM aerogel glass industry, promoting technological progress in areas such as energy conservation, environmental protection, and new energy utilization.

[0006] Therefore, this invention provides a method for preparing waterborne polyurethane phase change aerogel glass by combining aerogel materials, phase change materials, and glass. This method not only imparts good light transmittance to the phase change aerogel but also possesses other advantages of glass, such as weather resistance and mechanical strength. The phase change aerogel glass of this invention has broad application prospects in the construction field and is expected to play an important role in civil buildings, industrial plants, greenhouses, and other areas, improving the energy efficiency and comfort of buildings and promoting the development of green and environmentally friendly buildings. Summary of the Invention

[0007] To address the shortcomings of existing technologies, the main objective of this invention is to provide a waterborne polyurethane phase change aerogel glass and its preparation method. This waterborne polyurethane phase change aerogel glass combines the advantages of polyurethane, phase change materials, and aerogel, achieving both heat absorption and release while providing thermal insulation. It can efficiently absorb and utilize solar energy in winter and effectively insulate against solar radiation heat in summer, thereby reducing building energy consumption.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A waterborne polyurethane phase change aerogel glass includes upper and lower glass plates, a hydrophobic aerogel layer, and a hydrophilic aerogel layer loaded with waterborne polyurethane phase change material. The hydrophobic aerogel layer includes hydrophobic silica aerogel, and the hydrophilic aerogel layer loaded with waterborne polyurethane phase change material is composed of hydrophilic silica aerogel and waterborne polyurethane solid-solid phase change material.

[0009] The present invention also provides a method for preparing the aqueous polyurethane phase change aerogel glass, comprising the following steps: (1) Preparation of hydrophobic gel: Add hydrophobic silica aerogel sol to a glass plate mold to induce a sol-gel reaction and obtain the first layer of transparent wet gel. (2) Preparation of hydrophilic gel: After molding, a hydrophilic silica aerogel sol is injected into the first layer of transparent wet gel in the mold to obtain the second layer of transparent wet gel. (3) Solvent replacement: The transparent wet gel in the glass plate mold is placed in an ethanol solution for solvent replacement to obtain an alcohol gel; (4) Supercritical drying: The glass plate mold loaded with alcohol gel was subjected to supercritical carbon dioxide drying to obtain a transparent silica aerogel glass plate. (5) Phase change material adsorption: Aqueous polyurethane emulsion is dropped into the hydrophilic silica aerogel of the above transparent silica aerogel glass plate. After drying and natural cooling, an aqueous polyurethane phase change aerogel glass concave plate containing aqueous polyurethane solid-solid phase change material is obtained. (6) Encapsulation: The glass cover is attached to the concave plate of the waterborne polyurethane phase change aerogel glass to obtain the waterborne polyurethane phase change aerogel glass.

[0010] In the above technical solution, in step (1), the sol-gel reaction temperature is 10-40℃ and the reaction time is 20-300 min; The sol is one or more of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, methyltriethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane and their oligomers and partial hydrolysis products, ethanol, methanol, and cetyltrimethylammonium bromide.

[0011] In the above technical solution, in step (2), the sol-gel reaction temperature is 10-40℃ and the gelation time is 20-300 min; The sol is one or more of the following: tetraethyl orthosilicate, propyl orthosilicate, ethanol, methanol, acetic acid, ammonia, sodium fluoride, ammonium fluoride, and water.

[0012] In the above technical solution, in steps (1) and (2), the thickness of the transparent wet gel formed on the inner surface of the mold is 1 to 5 mm.

[0013] In the above technical solution, in step (3), the ethanol solution is a mixture of ethanol and water with a mass ratio of 1:(0.01~0.6).

[0014] In the above technical solution, in step (4), the temperature of the supercritical carbon dioxide drying is 35~60℃ and the drying time is 6~24h.

[0015] In the above technical solution, in step (5), the drying temperature is 40-60℃ and the drying time is 7-9h.

[0016] In the above technical solution, the hydrophilic aerogel has a nanoscale porous structure and serves as a carrier for the aqueous polyurethane phase change material. The aqueous polyurethane solid-solid phase change material loaded therein regulates the temperature by absorbing or releasing the latent heat of phase change.

[0017] The aerogel glass of the present invention contains an aqueous polyurethane energy storage phase change material, which can absorb or release heat within a specific temperature range. Furthermore, due to the use of water as a dispersion medium, it has advantages such as being environmentally friendly, safe, and easy to process, and has wide applications in the field of building energy conservation.

[0018] Compared with the prior art, the present invention has the following beneficial effects: The waterborne polyurethane phase change aerogel glass of this invention actively regulates indoor temperature through a phase change process. A silica aerogel layer isolates the indoor environment from external temperatures, significantly reducing energy consumption for indoor heating and cooling. The hydrophilic aerogel layer acts as a carrier for the waterborne polyurethane phase change material, which regulates temperature by absorbing or releasing latent heat of phase change. It provides excellent thermal insulation when there is a large temperature difference between the inside and outside of the building, while also absorbing and releasing heat. It efficiently absorbs and utilizes solar energy in winter and effectively blocks solar radiation in summer, making it significant for reducing building energy consumption. Attached Figure Description

[0019] The present invention will be further described below with reference to the accompanying drawings and embodiments: Figure 1 The present invention relates to an aqueous polyurethane phase change aerogel glass; In the figure: upper glass plate 1, hydrophobic silica aerogel layer 2, hydrophilic silica aerogel layer 3 loaded with waterborne polyurethane solid-solid phase change material, glass concave plate 4, lower glass plate 5. Figure 2 This is a schematic diagram of the preparation of the aqueous polyurethane phase change aerogel glass of the present invention. Detailed Implementation

[0020] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0021] like Figure 1 As shown, the waterborne polyurethane solid-solid phase change aerogel glass of the present invention comprises, in sequence: an upper glass plate 1, a hydrophobic aerogel layer 2, a hydrophilic aerogel layer 3 loaded with waterborne polyurethane solid-solid phase change material, a concave glass plate 4, and a lower glass plate 5; the hydrophobic aerogel layer 3 comprises hydrophobic silica aerogel, and the hydrophilic aerogel layer loaded with waterborne polyurethane solid-solid phase change material is composed of hydrophilic silica aerogel and waterborne polyurethane solid-solid phase change material.

[0022] The aerogel glass of this invention actively regulates indoor temperature through a phase change process. A hydrophobic silica aerogel layer 2 isolates the indoor environment from external temperatures, significantly reducing energy consumption for indoor heating and cooling. The hydrophilic aerogel layer serves as a carrier 3 for the waterborne polyurethane phase change material, which absorbs or releases latent heat of phase change to regulate temperature. It provides excellent thermal insulation when there is a large temperature difference between the inside and outside of the building, while also absorbing and releasing heat. In winter, it efficiently absorbs and utilizes solar energy, and in summer, it effectively blocks solar radiation, making it significant for reducing building energy consumption.

[0023] The technical solution of the present invention will be described in detail below with reference to the embodiments.

[0024] Example 1: A waterborne polyurethane phase change aerogel glass includes the following steps: (1) Preparation of hydrophobic gel: Add hydrophobic silica aerogel sol to a glass plate mold to induce a sol-gel reaction and obtain the first layer of transparent wet gel with a thickness of 5 mm. The hydrophobic silica aerogel was prepared as follows: 0.1 mol / L acetic acid was added to the sol to adjust the pH to 4-5. After hydrolysis at 60°C for 8 hours, 0.3 mol / L sodium hydroxide was added to adjust the pH to 8-9 for gelation. The sol consisted of 60 parts tetraethyl orthosilicate, 64 parts methyltriethoxysilane, 4 parts pure water, 100 parts ethanol, and 0.6 parts hexadecyltrimethylammonium bromide (by molar weight). (2) Preparation of hydrophilic gel: After the hydrophobic gel is formed, the second layer of hydrophilic silica aerogel sol is injected into the first layer of transparent wet gel in the mold to obtain the second layer of transparent wet gel with a gel thickness of 5 mm. The sol is composed of 1 part tetraethyl orthosilicate, 12 parts pure water, 33 parts ethanol, 0.12 parts ammonia, and 0.076 parts sodium fluoride by molar amount. (3) Solvent replacement: The transparent wet gel in the glass plate mold is placed in a mixed solution of ethanol and water with a mass ratio of 80:20 for solvent replacement to obtain an alcohol gel; (4) Supercritical drying: The glass plate mold loaded with alcohol gel was placed in a drying kettle and dried with supercritical carbon dioxide at 50°C for 8 hours to obtain a transparent silica aerogel glass plate.

[0025] (5) Phase change material adsorption: Based on the volume of the second layer of hydrophilic silica aerogel, at 2 g / cm³... 3The adsorption amount of waterborne polyurethane emulsion was calculated by adding it dropwise into the second layer of hydrophilic silica aerogel in a transparent silica aerogel glass plate. Then, it was transferred to a constant temperature oven at 50°C for 8 hours. Finally, it was taken out and allowed to cool naturally to obtain a waterborne polyurethane phase change aerogel glass concave plate containing waterborne polyurethane solid-solid phase change material.

[0026] (6) Packaging: ... Figure 1 The glass cover plate shown is attached to the concave plate of waterborne polyurethane phase change aerogel glass to obtain waterborne polyurethane phase change aerogel glass with a light transmittance of 85%.

[0027] Example 2: (1) Preparation of hydrophobic gel: A hydrophobic silica aerogel sol is added to the glass plate mold to cause a sol-gel reaction, resulting in a transparent wet gel with a gel thickness of 3 mm. The method for preparing the hydrophobic silica aerogel sol is as follows: 0.1 mol / L acetic acid is added to the sol to adjust the pH to 4-5, and hydrolysis is carried out at 60℃ for 8 hours. Then, 0.3 mol / L sodium hydroxide is added to adjust the pH to 8-9 to induce gelation. The sol consists of 48 parts of tetraethyl orthosilicate, 72 parts of phenyltriethoxysilane, 6 parts of pure water, 96 parts of ethanol, and 0.8 parts of hexadecyltrimethylammonium bromide by molar weight. (2) Preparation of hydrophilic gel: After molding, the second layer of hydrophilic silica aerogel sol is injected into the first layer of transparent wet gel in the mold to obtain the second layer of transparent wet gel with a gel thickness of 3 mm. The sol is composed of 3 parts methyl orthosilicate, 12 parts pure water, 35 parts ethanol, 0.17 parts ammonia, and 0.04 parts sodium fluoride by molar amount. (3) Solvent replacement: The transparent wet gel in the glass plate mold is placed in a mixed solution of ethanol and water with a mass ratio of 80:20 for solvent replacement to obtain an alcohol gel; (4) Supercritical drying: The glass plate mold together with the alcohol gel is placed in a drying kettle at a temperature of 50°C and dried for 8 hours to obtain a transparent silica aerogel glass plate.

[0028] (5) Phase change material adsorption: Based on the volume of the second layer of hydrophilic silica aerogel, the adsorption amount is calculated with a waterborne polyurethane emulsion ratio of 2 g / cm3. The adsorption is added dropwise into the second layer of hydrophilic silica aerogel in the transparent silica aerogel glass plate. Then, it is transferred to a constant temperature oven at 50℃ for 8 hours. Finally, it is taken out and allowed to cool naturally to obtain a waterborne polyurethane phase change aerogel glass concave plate containing waterborne polyurethane solid-solid phase change material.

[0029] (6) Encapsulation: The glass cover is attached to the concave plate of the waterborne polyurethane phase change aerogel glass to obtain the waterborne polyurethane phase change aerogel glass.

[0030] Example 3: The same preparation method as in Example 1 was used, with the only difference being that the gel thicknesses were 1 mm, 2 mm, 3 mm, and 4 mm. The effect of different gel thicknesses on the transmittance of the waterborne polyurethane phase change aerogel glass was investigated, and the results are shown in Table 1.

[0031] Table 1

[0032] As shown in Table 1, the light transmittance of waterborne polyurethane phase change aerogel glass decreases with increasing aerogel thickness. Therefore, the light transmittance of aerogel glass can be controlled by selecting an appropriate aerogel thickness.

[0033] Comparative Example 1: Comparative Example 1 is basically the same as Example 1, except that the phase change material in step (5) is not added.

[0034] Comparative Example 2: Comparative Example 2 is basically the same as Example 2, except that in step (3), the transparent wet gel in the glass plate mold is placed in a mixed solution of ethanol and water in a mass ratio of 20:80 for solvent replacement.

[0035] The performance of the aqueous polyurethane phase change aerogel glasses prepared in Examples 1-2 and Comparative Examples 1-2 was tested, and the results are shown in Table 2.

[0036] Table 2. Performance test results of the aerogel glasses prepared in Examples 1-2 and Comparative Examples 1-2

[0037] As shown in Table 2, the waterborne polyurethane phase change aerogel glass of the present invention isolates the indoor environment from the influence of the external temperature of the building through the hydrophobic silica aerogel layer, while adsorbing the waterborne polyurethane emulsion into the hydrophilic aerogel layer. The temperature is regulated by the heat absorption or release of the waterborne polyurethane solid-solid phase change material, thereby reducing building energy consumption. It has broad application prospects in the construction field.

[0038] The above embodiments are merely preferred technical solutions of the present invention and should not be considered as limitations on the present invention. The scope of protection of the present invention should be limited to the technical solutions described in the claims, including equivalent substitutions of the technical features described in the claims. That is, equivalent substitutions and improvements within this scope are also within the scope of protection of the present invention.

Claims

1. A waterborne polyurethane phase change aerogel glass, characterized in that, The aerogel glass includes upper and lower glass plates, a hydrophobic aerogel layer, and a hydrophilic aerogel layer loaded with a waterborne polyurethane phase change material. The hydrophilic aerogel layer loaded with the waterborne polyurethane phase change material is composed of hydrophilic silica aerogel and a waterborne polyurethane solid-solid phase change material. The method for preparing the aqueous polyurethane phase change aerogel glass includes the following steps: (1) Preparation of hydrophobic gel: Add hydrophobic silica aerogel sol to a concave glass plate mold to induce a sol-gel reaction and obtain the first layer of transparent wet gel. (2) Preparation of hydrophilic gel: The hydrophilic silica aerogel sol is injected into the first layer of transparent wet gel in the mold to cause a sol-gel reaction, and the second layer of transparent wet gel is obtained. (3) Solvent replacement: The transparent wet gel in the glass plate mold is placed in an ethanol solution for solvent replacement to obtain an alcohol gel; The ethanol solution is a mixture of ethanol and water in a mass ratio of 1:(0.01-0.6); (4) Supercritical drying: The glass plate mold loaded with alcohol gel was subjected to supercritical carbon dioxide drying to obtain a transparent silica aerogel glass plate. The temperature for supercritical carbon dioxide drying is 35-60℃, and the drying time is 6-24h. (5) Phase change material adsorption: Aqueous polyurethane emulsion is dropped into the hydrophilic silica aerogel of the above transparent silica aerogel glass plate. After drying and natural cooling, an aqueous polyurethane phase change aerogel glass concave plate containing aqueous polyurethane solid-solid phase change material is obtained. (6) Encapsulation: The glass cover is attached to the concave plate of the waterborne polyurethane phase change aerogel glass to obtain the waterborne polyurethane phase change aerogel glass.

2. The aqueous polyurethane phase change aerogel glass according to claim 1, characterized in that, In step (1), the temperature of the sol-gel reaction is 10-40℃ and the reaction time is 20-300min.

3. The aqueous polyurethane phase change aerogel glass according to claim 1, characterized in that, In step (2), the sol-gel reaction temperature is 10-40℃ and the gelation time is 20-300min.

4. The aqueous polyurethane phase change aerogel glass according to claim 1, characterized in that, In steps (1) and (2), the thickness of the transparent wet gel formed on the inner surface of the mold is 1-5 mm, respectively.

5. The aqueous polyurethane phase change aerogel glass according to claim 1, characterized in that, In step (5), the drying temperature is 40-60℃ and the drying time is 7-9h.

Citation Information

Patent Citations

  • Integrated transparent thermal insulation SiO2 aerogel composite glass and preparation method thereof

    CN102180603A

  • Aqueous polyurethane phase change energy storage material

    CN103992461A

  • Novel cigarette heater provided with aerogel heat-insulating layer

    CN104223359A